TIME VARYING BETA (DUAL BETA): CONDITIONAL MARKET TIMING CAPM - Rachmat Sudarsono; Suad Husnan; Eduardus Tandelilin; Erni Ekawati (Journal of Management and Business, 2012)
Dual beta became a debate between researchers in finance especially investment and portfolio. This research test CAPM using dual beta predictions in conditional market timing. The research tested unconditional and conditional Beta, that showed linear and positive affect of return toward risk on single and multiperiods. The beta’s slope skewed but with moderate skewness, and there is no zero beta. However if the investors have les diversified portfolio, its show idiosyncratic risk and systematic risk determine the securities pricing model. Conditional beta test, showed positive slope for SML on bullish market, and negative for bearish market. There is also showed a shock to volatility because of leverage effect and or volatility feedback. The responsiveness of positive shock (bullish market) and negative (bearish market) is positive, however the magnitude of SML slope higher for bearish than bullish market. Dual beta remains consistent in explaining positive effect of risk and return. Dual beta able to reduce the idiosyncratic risk on bearish market rather than on bullish market.